Enhancing diagnostics through flow cytometry: overcoming barriers in low resource settings - Alfaro, Jeanine; Valverde, Patricia; Salguero, Paola; Arevalo, Xiomara; Ortega, Pamela; Sanchez, Luisa; Antillon-Klussmann, Federico; Hayden, Randall T.; Rodriguez, Alicia; Metzger, Monika L.; Choi, John K.; Santana, Victor M.; et al. (Frontiers in Oncology, 2025)
Despite advancements in the treatment of acute lymphoblastic leukemia (ALL), survival rates vary greatly based on factors such as cancer subtype and geographical location. The use of diagnostic tools like immunophenotyping and measurable residual disease (MRD) detection by flow cytometry (FC) are key to optimal management. FC offers higher sensitivity and rapid turnaround compared to traditional methods like morphological evaluation and immunohistochemistry. However, in low- and middle-income countries (LMIC), the adoption of robust MRD assays via FC remains limited due to challenges such as technical complexity, the need for operator expertise, and the high costs associated with antibodies and quality control. This study discusses the design, implementation, and validation of MRD strategies using FC in resource-constrained environments, highlighting the potential for improved accessibility and patient outcomes when these barriers are addressed.